2016
DOI: 10.21511/pmf.5(3).2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Work satisfaction of municipality employees while performing duties under the conditions of limited financial resources

Abstract: The purpose of the study on which this article reports is to use affective events theory as a theoretical framework to develop a model that could be used by municipal supervisors to create an environment conducive to working. The study comprised 227 non-management, middle managers and senior managers in a municipality. Confirmatory factor analysis (CFA) and structural equation modelling (SEM) were used to analyze the data. There was a low negative correlation between supervisory support and job satisfaction. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In the same vein, affective variables and affective commitment are distinguishable (Wegge et al, 2006). Such hypotheses have been confirmed by two other studies conducted at one municipality in Mpumalanga (Maleka et al, 2016b). Several studies have tested the relationship between the study variables, and the hypotheses developed from these studies for the research reported on in this article are shown (Table 1).…”
Section: Purpose Of the Studysupporting
confidence: 72%
See 4 more Smart Citations
“…In the same vein, affective variables and affective commitment are distinguishable (Wegge et al, 2006). Such hypotheses have been confirmed by two other studies conducted at one municipality in Mpumalanga (Maleka et al, 2016b). Several studies have tested the relationship between the study variables, and the hypotheses developed from these studies for the research reported on in this article are shown (Table 1).…”
Section: Purpose Of the Studysupporting
confidence: 72%
“…Secondly, a theoretical contribution was made as employee performance, which had not been included in the study conducted by Wegge et al (2006), was added as independent variable. This variable is salient in the municipality context because previous research has revealed that, when employees are given proper feedback, coached and given training opportunities, they are most likely to offer customers excellent service (Maleka et al, 2016b). The data also showed that this variable was the greatest predictor of positive emotions.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations